Is Duane retraction syndrome part of the VACTERL association? - Akar, Serpil (Dove Medical Press, 2013)
We report here a patient with type 1 Duane’s retraction syndrome and multiple congenital abnormalities as a result of the VACTERL association. The presented combination of Duane’s retraction syndrome and the VACTERL association has not been reported in the literature. The present case was instructive for reviewing the continuous spectrum of ocular anomalies that accompany the VACTERL association.